2009
DOI: 10.1128/iai.01455-08
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Toll-Like Receptor 2 (TLR2) and TLR4 Responses byAspergillus fumigatus

Abstract: Toll-like receptor (TLR)-based signaling pathways in the host may be modulated by pathogens during the course of infection. We describe a novel immunomodulatory mechanism in which Aspergillus fumigatus conidia induce attenuation of TLR2-and TLR4-mediated interleukin (IL)-6 and IL-1␤ proinflammatory responses in human mononuclear cells with suppression of IL-1␤ mRNA transcription. Background TLR2 and TLR4 mRNA transcription was not influenced. A. fumigatus conidia induced TLR2 internalization and uptake into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 45 publications
2
70
0
1
Order By: Relevance
“…There are, however, several examples demonstrating that cell signaling can influence endocytosis and vice versa (20,23). Indeed, TLR4 was shown to actively participate in bacterial phagocytosis (4) and to be rapidly internalized by human monocytes after in vitro interaction with P. brasiliensis yeasts or A. fumigatus conidia (10,21). In addition, a recent paper has clearly demonstrated that TLR4 and TLR2 synergize with class A scavenger receptor to mediate phagocytosis of Gram-negative and Gram-positive bacteria, respectively (3).…”
Section: Fig 4 Increased Numbers Of Activated Macrophages Cd4mentioning
confidence: 99%
“…There are, however, several examples demonstrating that cell signaling can influence endocytosis and vice versa (20,23). Indeed, TLR4 was shown to actively participate in bacterial phagocytosis (4) and to be rapidly internalized by human monocytes after in vitro interaction with P. brasiliensis yeasts or A. fumigatus conidia (10,21). In addition, a recent paper has clearly demonstrated that TLR4 and TLR2 synergize with class A scavenger receptor to mediate phagocytosis of Gram-negative and Gram-positive bacteria, respectively (3).…”
Section: Fig 4 Increased Numbers Of Activated Macrophages Cd4mentioning
confidence: 99%
“…TLR1 -4, 6, 7, and 9 recognize a variety of fungal species through mostly undefined ligands (Netea et al 2004b;Biondo et al 2005Biondo et al , 2011Chai et al 2009;Kasperkovitz et al 2010;Bourgeois et al 2011). The main TLRs involved in sensing fungal ligands are TLR2, TLR4, and TLR9 that recognize zymosan, phospholipomannan, O-linked mannans, glucoronoxylomannan, and fungal DNA (Shoham et al 2001;Brown 2011;Romani 2011).…”
Section: Pattern-recognition Receptorsmentioning
confidence: 99%
“…Conidia and hyphae were prepared and heat-inactivated (HI) as described previously (22). A concentration of 1 3 10 7 /ml was used in the experiments.…”
Section: Aspergillusmentioning
confidence: 99%